Optimization of γ-aminobutyric acid production by Lactobacillus plantarum Taj-Apis362 from honeybees - Tajabadi, Naser (MDPI, 2015)
Dominant strains of lactic acid bacteria (LAB) isolated from honey bees were evaluated for their γ-aminobutyric acid (GABA)-producing ability. Out of 24 strains, strain Taj-Apis362 showed the highest GABA-producing ability (1.76 mM) in MRS broth containing 50 mM initial glutamic acid cultured for 60 h. Effects of fermentation parameters, including initial glutamic acid level, culture temperature, initial pH and incubation time on GABA production were investigated via a single parameter optimization strategy. The optimal fermentation condition for GABA production was modeled using response surface methodology (RSM). The results showed that the culture temperature was the most significant factor for GABA production. The optimum conditions for maximum GABA production by Lactobacillus plantarum Taj-Apis362 were an initial glutamic acid concentration of 497.97 mM, culture temperature of 36 °C, initial pH of 5.31 and incubation time of 60 h, which produced 7.15 mM of GABA. The value is comparable with the predicted value of 7.21 mM.